Evaluation of the Non-Formal Education Equivalency Program in Addressing School Dropouts at Sanggar Kegiatan Belajar (SKB) Kota Bangun - Fitriani; Mulawarman, Widyatmike Gede; Warman; Azainil; Masruhim, Muh. Amir; Sudarman (PT ARRUS Intelektual Indonesia, 2025)
School dropouts pose a significant challenge within the education system, requiring sustained intervention. The non-formal education equivalency program organized by the Learning Activity Center (SKB) serves as a crucial solution to provide re-access to education for dropouts. Therefore, this research aims to evaluate the implementation and effectiveness of the Non Formal Education Equivalency Program in handling school dropouts at SKB Kota Bangun. This evaluation covers stakeholder perceptions regarding the program's success, benefits perceived by students, and its contribution to providing a second chance in education. This research employed a qualitative approach with an evaluative study method. Data collection was conducted through in-depth interviews with key stakeholders, namely the Head of SKB, Tutors, and Students of the equivalency program, supported by document studies related to the program. Data analysis was performed descriptively-qualitatively to interpret findings regarding the implementation, results, and impact of the equivalency program at SKB Kota Bangun. The research findings indicate that the Non-Formal Education Equivalency Program at SKB Kota Bangun is considered successful by the management and highly beneficial by the students. This program effectively serves as a vehicle for school dropouts to continue their education and obtain an equivalency diploma (Package A, B, or C), which is considered vital for job seeking and future planning. Students perceive benefits not only in the form of diploma acquisition but also in increased knowledge, skills, and the expansion of social networks. Although potential challenges in implementation are acknowledged, the program's fundamental goal of providing a second chance and addressing the school dropout issue is deemed to have been achieved. This evaluation concludes that the Equivalency Program at SKB Kota Bangun plays an important role in the local education system by providing an alternative pathway for school dropouts. The program's success in providing hope and opening future opportunities for students affirms its relevance. These findings are expected to provide constructive input for the management of SKB Kota Bangun and relevant policymakers for the quality improvement and sustainability of similar non-formal education programs.